Formulation of Rifampicin Suspension - Lubna A. Sabri; Alaa A. Abdul-Rasool; Muayad A. Shehab (College of Pharmacy University of Baghdad, 2017)
Rifampicin is the drug of choice in treatment of tuberculosis. Also, it is effective in treatment of various bacterial infections.This study was carried out to prepare a stable suspension for rifampicin through preparation of different formulas of rifampicin aqueous suspension either as ready to use or as granular powder to be reconstituted.The selected formula (A) was evaluated and compared with commercial brand of rifampicin (RifactineÂ®) as a reference through measuring their dissolution rates and other physical properties.The results indicated that the selected formula had better dissolution rate compared with the reference suspension and the rheogram showed that the selected formula was less viscous than the reference one.Also, it was found that the granular rifampicin was more stable than the ready to use suspension, since the expiration date of granular rifampicin was 2.6 years, while the expiration date of ready to use suspension was 1.8 years. Key words :Rifampicin , Suspending agent ,Powder for reconstitution , Aqueous suspension